Chemical composition and antimicrobial activity of the essential oil of Abies cephalonica Loudon from Mount Ainos (Kefalonia, Greece). Issue 2 (4th March 2022) - Tsasi, Gerasimia; Danalatos, Gerasimos; Tomou, Ekaterina-Michaela; Sakadani, Eleni; Bethanis, Mihalis; Kolokouris, Aristides; Samaras, Yiannis; Ćirić, Ana; Sokoviċ, Marina; Skaltsa, Helen
ABSTRACT: Abies cephalonica Loudon consists one of the three fir species occurring in Greece. The aim of this study was to evaluate the chemical composition of the essential oil (EO) from needles of A. cephalonica from Mt. Aenos (Kefalonia Island, Greece) and to investigate its antimicrobial activity. The EO was obtained by hydrodistillation and 68 constituents corresponding to 99.4% of the EO were identified by using GC-MS analysis. The major chemical category of the volatile compounds were the monoterpene hydrocarbons (63.9%), followed by oxygenated monoterpenes (20.2%). In particular, the main components were β-pinene (26.9%), bornyl acetate (12.5%), α-pinene (10.1%), camphene (9.2%), limonene (8.1%), γ-eudesmol (8.1%) and β-phellandrene (5.8%). To the best of our knowledge, the present study is the first research, reporting the phytochemical profile and the antimicrobial potential of the EO of A. cephalonica from this distinct geographic area.